2015
DOI: 10.14723/tmrsj.40.175
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Self-Assembly of His-tag Hybrid of Substrate-Binging Short Domain in Transient Receptor Potential Vanilloid Type 1 for Vanillin Sensing Application

Abstract: The amino acid sequence of vanillin-binding site of transient receptor potential vanilloid type 1 from rat, Leu 544 -Tyr 553 , was extracted and hybridized with His-tag. The hexadecamer invariant chain peptide, Leu-Ala-Met-Gly-Trp-Thr-Asn-Met-Leu-Tyr-His-His-His-His-His-His (VBH), was prepared by solid-phase peptide synthesis. Circular dichroic spectral measurements determined the α-helix content to be 17%, which was consistent to that of short peptides. In a combined use of thiol-derivatized nitrilotriacetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The obtained data were rather small compared with the theoretical data for alkanethiol (760 pmol cm –2 ). The sterically bulky aminopolycarboxyl group might hinder molecular association at the surface, but previous AFM study showed that SNTA developed well-organized SAMs . During the chelation of S3HS4 , the resonance frequency decreased further (Figure ), eventually reaching equilibrium at a specific binding amount of 84 ± 47 pmol cm –2 ( n = 3), which was considerably smaller than that of SNTA at the surface.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…The obtained data were rather small compared with the theoretical data for alkanethiol (760 pmol cm –2 ). The sterically bulky aminopolycarboxyl group might hinder molecular association at the surface, but previous AFM study showed that SNTA developed well-organized SAMs . During the chelation of S3HS4 , the resonance frequency decreased further (Figure ), eventually reaching equilibrium at a specific binding amount of 84 ± 47 pmol cm –2 ( n = 3), which was considerably smaller than that of SNTA at the surface.…”
Section: Resultsmentioning
confidence: 86%
“…Repeated experiments with various QCM-chip preparations revealed that capsaicin bound 78 ± 19% ( n = 5) of the surface-attached S3HS4 , from which was obtained an apparent binding constant of (4.2 ± 3.6) × 10 4 M –1 . A previous report showed that S4H , a single-helix host, selectively bound vanillin with an apparent binding constant of 2.7 × 10 3 M –1 . For comparison, we investigated the capsaicin response at an Au-chip with a HS4 /SNTA/Au interfacial structure but no frequency response was confirmed (Figure E).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations